DEPRESI DAN TERAPI KOGNITIF-PERILAKU PADA WANITA PENDERITA HIV/AIDS YANG TERINFEKSI DARI SUAMINYA - Atmasari, Lutfi (IAIN Kediri, 2016)
The purpose of this study is to explore the effectiveness of cognitive-behavioral therapy to women depression who are living with HIV that’s infected by her husband. This study involved two variables, depression as dependent variable and cognitive-behavioral therapy as independent variable. Depression is emotional condition that following attibutes: spesific alteration in mood, a negative self-concept, regressive and self-punitive wishes, vegetative changes, and change in activity level. While cognitive-behavioral therapy is a cognitive and behavioral therapy for helping depression. Cognitive therapy is used for changing the maladaptive thought, and behavioral therapy is used for relaxing the body and brain or decreasing the physical problems.This study was pre-experimental study that involved two depression women who living with HIV, that’s infected by her husband. Beck Depression Inventory is used for collecting data, it consists of 21 statements to determine the depression of women who living with HIV, that’s infected by her husband. Data analysis was done by non-parametric analysis, and the technique for calculated data was Wicoxon signed-rank test with SPSS 18.00 for windows.The calculation of Wicoxon signed-rank test based on the positive ranks was z = -1.342 and the result of the significance was p = 0.180(p < 0.05). It explained that the treatment was not effective for decrease the depression of women who living with HIV, that’s infected by her husband. However, that result was contrary with the real condition that the scores of BDI showed the reducing of depression. That result was also supported by the interview records. Keywords; Cognitive-Behavioral Therapy, Depression, Women living with HIV that’s infected by her husband.